Theoretical and practical aspects of pedagogy and psychology - Moskatova A. K., Gordeeva E. N., Lavina T. A., Zakharova A. N., Gritskevich T. I., Goriachevskaia E. V., Safonova M. V., Levchenko V. V., Lapshova E. S., Meshechkina R. P., Vysochinenko A. S., Ustinova E. M., Shilenko S. I., Zaritskaia V. V., Dzokaeva Z. M., Pavliuchenok M. B., Uliankova N. A., Sokolova G. A., Genvareva I. A., Marchenkova N. G., Leont'eva L. N., Sudakov O. V., Sudakov D. V., Belov E. V., Gordeeva O. I., Kretinina L. V., Sorokoumova G. V., Mychko E. I., Strelnikova E. S., Kumaeva M. V., Bulat R. E., Sharipova A. P. (Theoretical and practical aspects of pedagogy and psychology, 2022)
the chapter discusses the topic of the possibility of increasing professional motivation in the process of group counseling and suggests one of the options for the consultation program. The relevance of the study of group consultations as a means of increasing the professional motivation of retail employees is dictated by the peculiarity of the conditions of the modern market, where the demand for personnel significantly exceeds the supply. A study was conducted on the basis of an organization engaged in retail trade. 30 people took part in the experiment. In the course of the work, the theoretical and methodological foundations and approaches in the direction of studying motivation in general and staff motivation in particular were studied. The author has developed and tested a program of group psychological counseling in order to increase the professional motivation of the organization's staff. As a result of the formative experiment, it was possible to develop in the group participants a desire to master new knowledge, change their attitude to increased requirements, be interested in responsible and difficult tasks, take responsibility in work and decision-making, develop purposefulness and perseverance in achieving goals, increase the desire for professional growth.
Keywords: мотивация; motivation; повышение профессиональной мотивации; программа консультаций; professional motivation enhancement; consultation program